Eksistensi Gamelan Gong Gede Saih Pitu Dalam Ritual Agama Hindu Di Banjar Kebon Singapadu ( Perspektif Teologi Hindu ) - I Wayan Darya (Jayapangus Press, 2019)
Types of gamelan that exist in the earth comes from the voice of Genta Pinara Pitu which became the inspiration of the birth gamelan in the realms of the Gods, Rsi, and also on the nature of Bhuta Kala. Furthermore, humans are also inspired to create various types of gamelan, including gamelan Gong Gede Saih Pitu in Banjar Kebon Singapadu. Gamelan can be used as a ritual medium that essentially has a deep theological meaning. Tones of the gamelan are the nyasa (sacred symbols) of the ista dewata who control all directions which form a circle called the pemgider bhuana. Playing one tone means having direct contact with one of the gods. However, the understanding of the existence of Gamelan Gong Gede Saih Pitu about the concept of ideas, structure, barrel, patih / saih, and the type of tetabuhan that it uses, need to be studied further to deepen the existence of Gong Gede Saih Pitu gamelan in Hindu theological perspective hindu ritual. This research uses qualitative research method with theological approach. Problem solving using Structural Theory, Symbol Theory, and Structural Functional Theory to dissect the gamelan's theatrical structure, function, and meaning of Gong Gede Saih Pitu in Banjar Kebon Singapadu. Data obtained from the text and obtained in the field through observation and interview, then processed and analyzed in accordance with the theory used with the method of theological approach, then obtained the result that the gamelan Gong Gede Saih Pitu as a form of art that developed today, has the theological concept derived from the sound of pale pent in the pangider bhuana circle, and its existence not only as an accompaniment of ritual procession and as a cultural development, but has a religious function and psychological function, and contains philosophical-theological meaning, aesthetic meaning, and grandeur, and dignity, which shows how great the concept of the gamelan is as the implementation of Hindu theological tones. Through the results of this research will materialize the understanding of gamelan theology contained in the lontar Prakempa and Aji Gurnitha, and dismissed the notion of the use of gamelan in Hindu rituals as a tradition of mule keto which is identical with the euphoria of splendor to enliven the atmosphere of the ceremony.